Implementasi Ijtihad Ittiba’ dan Talfiq Dalam Ekonomi Islam - Anriza Witi Nasution; Sudirman Suparmin; Tuti Anggraini (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2022)
Human life and its concepts continue to change along with the times, which causes the needs and problems of life to also develop. Various new problems, especially in the field of economics, which have not been answered in the era of previous scholars, have led to the need for ijtihad as a solution. On the other hand, we cannot be separated from doing ittiba' and talfiq in economic activities in order to avoid prohibited acts. Knowing the implementation of ijtihad, ittiba', and talfiq in Islamic economics is done through qualitative research using the literature study method. From the results of the literature review, it was found that the implementation of ijtihad, ittiba', and talfiq in Islamic economics has been carried out. The implementation of ijtihad is carried out through the issuance of fatwas by Ulama, ittiba' such as avoiding usury is implemented through the use of Islamic financial institutions, while talfiq is implemented through the sale and purchase of foreign currencies.